The determinants of recovery from the Black Saturday bushfire: demographic factors, behavioural characteristics and financial literacy. (24th November 2019) - Asbi, Ammar; Ramiah, Vikash; Yu, Xi; Wallace, Damien; Moosa, Nisreen; Reddy, Krishna
Abstract: We investigate the contribution of demographic factors, behavioural characteristics and financial literacy to recovery from the financial losses inflicted by the Black Saturday bushfire. Behavioural characteristics (such as overconfidence, self‐serving and loss aversion biases) in conjunction with bushfire survivors' knowledge of financial indicators are used to determine recovery time. Data are collected through in‐depth interviews with bushfire survivors, academics and experts in natural disasters. The results show that demographic, behavioural and financial literacy factors have the potential to enhance the recovery process.